Rethinking maize productivity considering the heterogeneity of maize farm households from Central and Southern Mexico - Camacho, Carolina (International Maize and Wheat Improvement Center, 2018)
Presented by Carolina Camacho (CIMMYT), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.